2013
DOI: 10.1182/blood-2012-11-469403
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between phenotype and genotype in a large unselected cohort of children with severe hemophilia A

Abstract: Key Points Previously untreated patients with severe hemophilia A caused by F8 null mutations show a more severe phenotype than previously untreated patients with non-null mutations. The phenotypic differences are modest, and as such not likely to affect decisions regarding when and how to start prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 23 publications
1
75
1
5
Order By: Relevance
“… Defined by intron 22 and intron 1 inversions, nonsense mutations, large deletions, small deletions/insertions outside poly‐A runs, or splice‐site mutations involving conserved nucleotides …”
Section: Resultsmentioning
confidence: 99%
“… Defined by intron 22 and intron 1 inversions, nonsense mutations, large deletions, small deletions/insertions outside poly‐A runs, or splice‐site mutations involving conserved nucleotides …”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Determination of the causative genetic variant in families affected by hemophilia is important for use in reproductive planning, for use in pregnancy and neonatal management, and also to inform risks of neutralizing antibody (inhibitor) formation and bleeding severity. [6][7][8][9][10][11][12] Therapies targeted to specific mutations have been studied and are likely to become more common in the future. 13 In 2012, 2 separate surveys, 1 distributed to hemophilia providers through the American Thrombosis Hemostasis Network (ATHN) and the other distributed to the patient community through the National Hemophilia Foundation, found that only ;20% of the hemophilia patients in the United States had had their genotype determined.…”
Section: Introductionmentioning
confidence: 99%
“…Hemophilia A is an X‐chromosome‐linked coagulation disorder that primarily affects males, and occurs in approximately 1 per 10,000 live births . It is caused by mutations and/or deletions in the F8 gene, resulting in a deficiency of factor VIII (FVIII) activity . Severe hemophilia A is defined as a coagulation activity of FVIII in plasma (FVIII:C) level <1% (<1 IU/dL), and individuals with this severe form of the disease experience recurrent spontaneous bleeding, primarily into the muscles and joints, leading to joint damage and severe disability .…”
mentioning
confidence: 99%